2021
DOI: 10.22323/2.20050205
|View full text |Cite
|
Sign up to set email alerts
|

How do we tackle the COVID-19 crisis? Mass media and psychological responses to the health crisis in Spain

Abstract: During global health crises, the mass media plays a key role in the construction of risk society. This paper analyses people's perception during the confinement in Spain regarding the role of mass media and its relationship with psychological responses and attitudes towards social control. Results from the survey (n=704) suggest that certain groups have been more affected by the messages distributed by the media, rendering them more vulnerable to suffering from negative psychological responses. The mass media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The findings of our study reveal that, in comparison to men, a majority of women report elevated levels of fear and anxiety. This finding is consistent with prior research that has consistently demonstrated higher levels of anxiety, fear, and psychological distress among women compared to men across various stages of the pandemic [ 21 , 24 , 25 , 31 , 32 , 33 , 34 , 35 ]. However, it is noteworthy that a decrease in the gender differences over time is documented in the study conducted by Fenollar-Cortés et al [ 36 ] in Spain between March and May 2020.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of our study reveal that, in comparison to men, a majority of women report elevated levels of fear and anxiety. This finding is consistent with prior research that has consistently demonstrated higher levels of anxiety, fear, and psychological distress among women compared to men across various stages of the pandemic [ 21 , 24 , 25 , 31 , 32 , 33 , 34 , 35 ]. However, it is noteworthy that a decrease in the gender differences over time is documented in the study conducted by Fenollar-Cortés et al [ 36 ] in Spain between March and May 2020.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, a potential side effect of public access to the analysis and monitoring instruments of epidemic trends could be a communication gap that may instill anxiety in the general public if the results are misinterpreted [ 28 ]. This is true especially if the information is improperly conveyed by the mass media and communication agencies [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, COVID-19 knowledge, risk perception, prior vaccine experience, and attitudes toward COVID-19 media messages have been identified as possible underlying psychosocial factors that may be associated with effective public health communication [10,11]. In addition, some studies have shown that younger individuals and women are more likely to engage in COVID-19 preventive behaviours in response to public health messages, pointing to the importance of considering demographic factors such as age and gender [12,13]. Socioeconomic factors such as income and education have been associated with the effectiveness of public health messages on COVID-19, indicating that people with lower income and educational levels were more likely to face barriers to accessing and understanding these messages [14].…”
Section: Introductionmentioning
confidence: 99%